Assessing future meteorological stresses for grain maize in France. (January 2018) - Caubel, J.; Garcia de Cortazar-Atauri, I.; Vivant, A.C.; Launay, M.; de Noblet-Ducoudré, N.
Abstract: Recent climate change has already affected maize cropping in France allowing for example earlier sowing dates in southern France and the growth of early season varieties in northern parts of the country. The climate will continue to evolve as discussed in all IPCC reports and there is a need for farmers, seed companies and agricultural cooperative corporations to be able to anticipate those changes. The ambition of our work is to provide them with the means to get ready to adapt by analyzing a) the time evolution of meteorological stresses and certain management practices throughout the crop's growth cycle, b) the impacts of climate-induced changes in calculated sowing dates on those stresses and practices. We have applied the method we developed in a former paper to study the climatic suitability of maize in two contrasted areas of France, Ile-de-France in the North and Midi-Pyrénées in the South. Three climate change scenarios, two climate models and two maize varieties distinct in terms of precocity were used to try and ensure meaningful results. Whatever the scenario, model and variety, maize will be sown earlier than it is currently the case in both regions, especially in Midi-Pyrénées. Whatever the sowing date, rising temperatures in the future will be favorable for late varieties in the current cooler areas, and therefore even farmers in Ile-de-France will be able to grow varieties with a wide range of crop cycle length. However heat and water stress will increase in both regions between flowering and maturity, irrespective of the sowing date and scenario, thereby limiting the possibility to achieve potential yields. In Midi-Pyrénées compromises will need to be found between early sowing to minimize some later stress and increasing risks of frost during emergence, that do not currently exist. Highlights: Future climate suitability of maize studied for two French areas and two varieties Dynamic method to compute sowing dates results in earlier sowing for both areas. Rising temperatures will favour late varieties in the current cooler areas. Heat and water stress will increase in both areas between flowering and maturity. Too early sowing will increase frost risks at emergence in the south.